Internationalization of East Asian Higher Education - Yun, Seungmin (Journal of International Students, 2015)
This edited volume entails several research studies examining the impact of globalization and internationalization within East Asian educational contexts. While most studies have focused on Westernized perspectives, the book attempts to provide a multidimensional view of globalization and competing arguments concerning internationalization in an East Asian context through international conferences and symposiums.